"Nested" cryptic diversity in a widespread marine ecosystem engineer: a challenge for detecting biological invasions - Claudio Fuentes Grunewald (BMC Evolutionary Biology, 2011)
Ecosystem engineers facilitate habitat formation and enhance biodiversity, but when they become invasive, they present a critical threat to native communities because they can drastically alter the receiving habitat. Management of such species thus needs to be a priority, but the poorly resolved taxonomy of many ecosystem engineers represents a major obstacle to correctly identifying them as being either native or introduced. We address this dilemma by studying the sea squirt Pyura stolonifera, an important ecosystem engineer that dominates coastal communities particularly in the southern hemisphere. Using DNA sequence data from four independently evolving loci, we aimed to determine levels of cryptic diversity, the invasive or native status of each regional population, and the most appropriate sampling design for identifying the geographic ranges of each evolutionary unit.